2016
DOI: 10.1080/14686996.2016.1148528
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of fabrication methods on spin relaxation and crystallite quality in Tm-doped Y3Al5O12 powders studied using spectral hole burning

Abstract: High-quality rare-earth-ion (REI) doped materials are a prerequisite for many applications such as quantum memories, ultra-high-resolution optical spectrum analyzers and information processing. Compared to bulk materials, REI doped powders offer low-cost fabrication and a greater range of accessible material systems. Here we show that crystal properties, such as nuclear spin lifetime, are strongly affected by mechanical treatment, and that spectral hole burning can serve as a sensitive method to characterize t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…For LiNbO 3 , some of the same measurements that reveal the large degradation in nanocrystals indicate that microcrystals have nearly the same properties as the bulk crystal [47]. In our previous SHB studies of Tm 3+ -doped yttrium aluminum garnet powders, we found that high-energy planetary ball milling dramatically affected 169 Tm 3+ nuclear hyperfine state lifetimes; however, we also found that the lifetimes were still significantly reduced in relatively large microcrystals produced by low-energy ball milling [49]. Since we expect crystal defects introduced by grinding to affect optical coherence properties more strongly than nuclear spin lifetimes due to the stronger coupling of the electronic states to the crystal lattice, optical coherence measurements should provide a uniquely sensitive method for probing even very low levels of crystal damage.…”
Section: Sample Preparationmentioning
confidence: 92%
See 1 more Smart Citation
“…For LiNbO 3 , some of the same measurements that reveal the large degradation in nanocrystals indicate that microcrystals have nearly the same properties as the bulk crystal [47]. In our previous SHB studies of Tm 3+ -doped yttrium aluminum garnet powders, we found that high-energy planetary ball milling dramatically affected 169 Tm 3+ nuclear hyperfine state lifetimes; however, we also found that the lifetimes were still significantly reduced in relatively large microcrystals produced by low-energy ball milling [49]. Since we expect crystal defects introduced by grinding to affect optical coherence properties more strongly than nuclear spin lifetimes due to the stronger coupling of the electronic states to the crystal lattice, optical coherence measurements should provide a uniquely sensitive method for probing even very low levels of crystal damage.…”
Section: Sample Preparationmentioning
confidence: 92%
“…Therefore, the usual characterization methods employed for REI-doped crystals such as 2PE, SHB, or FID are difficult to perform with powders. Previous measurements on powders have mostly employed detection of fluorescence emission to observe SHB [29,31,59], with direct transmission detection of SHB [49] and 2PE [36,37] only recently being successfully applied to powders. In particular, FID measurements on powders have not been previously reported to our knowledge.…”
Section: Optical Coherence Lifetime Measurementsmentioning
confidence: 99%
“…Strain induced by grinding and associated TLS could be the source of this significant broadening compared to the 80 kHz linewidth in the bulk crystal. Such mechanisms were also put forward in studies on Tm 3+ doped YAG crystals ground to micron size powders and probed by spectral hole burning [101]. The main effect of strain was observed on spectral hole lifetimes that are significantly shortened under milling (several hours down to 10 s of minutes) and could be partially recovered with high-temperature annealing.…”
Section: Nanocrystals and Polycrystalline Ceramic Materialsmentioning
confidence: 97%
“…Nano-materials can be obtained through different routes: nano-structures can be milled or etched from high-quality bulk materials, and nanocrystals can be obtained through chemical synthesis, mechanical crushing, or ablation techniques. The transition to nano-sized structures generally introduces detrimental effects such as poor crystal quality, surface effects, and amorphous behavior that can severely restrict practical applications [15,16]. While some of these effects, such as the increasing surface-to-volume ratio, are fundamental, others can be minimized by optimizing the fabrication process [15].…”
Section: Introductionmentioning
confidence: 99%
“…The transition to nano-sized structures generally introduces detrimental effects such as poor crystal quality, surface effects, and amorphous behavior that can severely restrict practical applications [15,16]. While some of these effects, such as the increasing surface-to-volume ratio, are fundamental, others can be minimized by optimizing the fabrication process [15]. Indeed, in some cases, both chemical synthesis as well as fabrication methods starting with bulk materials produced high-quality materials [17,18].…”
Section: Introductionmentioning
confidence: 99%